2007
DOI: 10.1159/000103660
|View full text |Cite
|
Sign up to set email alerts
|

Use of Topical Hemostatic Agents during Liver Resection

Abstract: Despite all recent developments in surgical techniques during liver surgery, blood loss is still one of the main causes for postoperative morbidity and mortality. Other complications include bile leakage and fluid accumulation intraperitoneally. Fibrin sealants are able not only to enhance clot formation and wound healing but possibly work as a sealing device for postoperative leakage and fistula formation. In this overview the underlying mechanisms for these agents are discussed and several clinical data conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 56 publications
0
43
0
4
Order By: Relevance
“…Based on their working mechanism, topical agents can be divided into three groups: agents that mimic coagulation (ie, fibrin sealants), agents that provide a matrix for endogenous coagulation (ie, collagen, gelatin, and cellulose sponges), and combined products that work as a matrix for endogenous and exogenous coagulation factors. 38,39 Current scientific evidence suggests beneficial effects in reducing the time to hemostasis and in lowering the requirements for perioperative RBC transfusions. [39][40][41][42][43] Although the beneficial effects of fibrin sealants have also been confirmed in a recent Cochrane review, 44 the efficacy of fibrin sealant in liver surgery has recently been questioned.…”
Section: Topical Hemostatic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their working mechanism, topical agents can be divided into three groups: agents that mimic coagulation (ie, fibrin sealants), agents that provide a matrix for endogenous coagulation (ie, collagen, gelatin, and cellulose sponges), and combined products that work as a matrix for endogenous and exogenous coagulation factors. 38,39 Current scientific evidence suggests beneficial effects in reducing the time to hemostasis and in lowering the requirements for perioperative RBC transfusions. [39][40][41][42][43] Although the beneficial effects of fibrin sealants have also been confirmed in a recent Cochrane review, 44 the efficacy of fibrin sealant in liver surgery has recently been questioned.…”
Section: Topical Hemostatic Agentsmentioning
confidence: 99%
“…38,39 Current scientific evidence suggests beneficial effects in reducing the time to hemostasis and in lowering the requirements for perioperative RBC transfusions. [39][40][41][42][43] Although the beneficial effects of fibrin sealants have also been confirmed in a recent Cochrane review, 44 the efficacy of fibrin sealant in liver surgery has recently been questioned. 45 In a large, randomized, controlled trial in 300 patients undergoing partial liver resection, Figueras and associates 45 found no difference in total blood loss, transfusion requirements, or postoperative morbidity between patients treated with fibrin sealants (n 5 150) and a control group without fibrin sealants (n 5 150).…”
Section: Topical Hemostatic Agentsmentioning
confidence: 99%
“…Therefore, covering the liver resection surface with a product that can seal both blood vessels and biliary radicals is an interesting concept. For this reason, fibrin sealants are widely used in liver surgery [5,6,7] despite scarce scientific evidence on the clinical effectiveness of these products [8,9]. The aim of this article is to review the literature on evidence of hemostatic and biliostatic capacities of different fibrin sealants in liver surgery.…”
Section: Introductionmentioning
confidence: 99%
“…While in Groups (B) and (C) the adhesion was moderate and light, respectively. patients' need for blood, which improve the postoperative prognosis (Berrevoet and de Hemptinne, 2007;Soltani et al, 2013;Jackson, 2001). Some of them require the natural functioning body's homeostatic system to provide a substrate for endogenous coagulation as Gelatin sponge ); others do not as aluminum chloride .…”
Section: Discussionmentioning
confidence: 99%